Macroabrasion and/or Partial Veneers: Techniques for the Removal of Localized White Spots - Ubiracy Gaião; Ana Carolina Portes Pasmadjian; Gabriela Resende Allig; Liliana Vicente Melo de Lucas Rezende; Vitória Beatriz Souza da Silva; Leonardo Fernandes da Cunha (Hindawi Limited, 2022)
Macroabrasion is a technique for the removal of localized white spots using a high-speed, intermittent high speed turbine finishing diamond tip. It is fast, safe, efficient, and an alternative to enamel microabrasion. However, when the stain is deeper, these localized intrinsic stains or defects can be treated with partial direct veneers. A conservative preparation should be done and that allows stratification of the resin to mask the hypoplasia and provide naturalness to the tooth. Thus, the objective of this work is to demonstrate, through a clinical case, macroabrasion and a partial veneer from the preparation, restoration, to the finishing and polishing to remove hypoplastic stains.